Water contact during courtship of males of Archisepsis diversiformis (Sepsidae) R. - Briceño Lobo, R D (Universidad de Costa Rica, 2002)
On uncut plants of Dieffenbachia (Araceae) male aggregations of Archisepsis diversiformis (Sepsidae) were observed fighting with each other and courting females. The males were observed repeatedly orienting toward water droplets, moving next to the droplet and leaning against it, alternatively, to the two sides of the body and using the legs from the opposite side to push against it. This movement was repeated up to seven times in one “bathing” event. The occasional “bath” probably helps to dissipate heat from the body surface, thus preventing a rise in body temperature.